Protocol of the Australasian Malignant Pleural Effusion-2 (AMPLE-2) trial: a multicentre randomised study of aggressive versus symptom-guided drainage via indwelling pleural catheters. Issue 7 (5th July 2016) - Azzopardi, Maree; Thomas, Rajesh; Muruganandan, Sanjeevan; Lam, David C L; Garske, Luke A; Kwan, Benjamin C H; Rashid Ali, Muhammad Redzwan S; Nguyen, Phan T; Yap, Elaine; Horwood, Fiona C; Ritchie, Alexander J; Bint, Michael; et al.
Abstract : Introduction: Malignant pleural effusions (MPEs) can complicate most cancers, causing dyspnoea and impairing quality of life (QoL). Indwelling pleural catheters (IPCs) are a novel management approach allowing ambulatory fluid drainage and are increasingly used as an alternative to pleurodesis. IPC drainage approaches vary greatly between centres. Some advocate aggressive (usually daily) removal of fluid to provide best symptom control and chance of spontaneous pleurodesis. Daily drainages however demand considerably more resources and may increase risks of complications. Others believe that MPE care is palliative and drainage should be performed only when patients become symptomatic (often weekly to monthly). Identifying the best drainage approach will optimise patient care and healthcare resource utilisation. Methods and analysis: A multicentre, open-label randomised trial. Patients with MPE will be randomised 1:1 to daily or symptom-guided drainage regimes after IPC insertion. Patient allocation to groups will be stratified for the cancer type (mesothelioma vs others), performance status (Eastern Cooperative Oncology Group status 0–1 vs ≥2), presence of trapped lung (vs not) and prior pleurodesis (vs not). The primary outcome is the mean daily dyspnoea score, measured by a 100 mm visual analogue scale (VAS) over the first 60 days. Secondary outcomes include benefits on physical activity levels, rate of spontaneous pleurodesis, complications, hospital admission days, healthcare costs and QoL measures. Enrolment of 86 participants will detect a mean difference of VAS score of 14 mm between the treatment arms (5% significance, 90% power) assuming a common between-group SD of 18.9 mm and a 10% lost to follow-up rate. Ethics and dissemination: The Sir Charles Gairdner Group Human Research Ethics Committee has approved the study (number 2015-043). Results will be published in peer-reviewed journals and presented at scientific meetings. Trial registration number: ACTRN12615000963527; Pre-results.